Self-evaluation of Thai adult learners in English writing practice - Kasma Suwanarak (Penerbit Universiti Kebangsaan Malaysia, 2018)
This research primarily aims to investigate how the Thai adult learners self-evaluate their English writing performance in relation to the teacher’s evaluation and what the students and the teacher experience from the evaluation practice. The participants were 32 Thai graduate students and a Thai English language teacher of an EFL (English as a foreign language) writing course. The data were collected through student’s selfevaluation and teacher’s evaluation forms, writing tasks, and individual interviews. The qualitative data were considered together with the quantitative data in order to gain the whole picture of the issue under investigation. The findings revealed that the adult learners (or students) were able to self-evaluate their writing performance. The goals set out in the course syllabus, concerning the students’ participation in writing process and evaluating their writing, were practical and the students were well aware of what their performance levels were. Having access to students’ self-evaluations also gave the teacher more useful information for judging their learning achievement. This research highlights the importance of students’ self-evaluation as a real and valid source of information for developing teaching EFL writing, and promoting the students to be autonomous and lifelong learners. Implications are drawn regarding the independent learning goals and recommendations for future research.